Ferroptosis-Inducing Nanomedicine for Cancer Therapy - Yang Wang; Yang Wang; Yang Wang; Tianfu Liu; Tianfu Liu; Tianfu Liu; Tianfu Liu; Xiang Li; Xiang Li; Xiang Li; Xiang Li; Hui Sheng; et al. (Frontiers Media S.A., 2021)
Ferroptosis, a new iron- and reactive oxygen species-dependent form of regulated cell death, has attracted much attention in the therapy of various types of tumors. With the development of nanomaterials, more and more evidence shows the potential of ferroptosis combined with nanomaterials for cancer therapy. Recently, there has been much effort to develop ferroptosis-inducing nanomedicine, specially combined with the conventional or emerging therapy. Therefore, it is necessary to outline the previous work on ferroptosis-inducing nanomedicine and clarify directions for improvement and application to cancer therapy in the future. In this review, we will comprehensively focus on the strategies of cancer therapy based on ferroptosis-inducing nanomedicine currently, elaborate on the design ideas of synthesis, analyze the advantages and limitations, and finally look forward to the future perspective on the emerging field.